Critical Perspectives on Maqashid al-Shariah in Modern Financial Systems - Mutia Febrina Sari; Ferdi Prayoga (GIC Proceeding, 2025)
This study offers Critical Perspectives on Maqashid al-Shariah in Modern Financial Systems, delving into the theoretical foundations and practical applications of Islamic legal objectives within contemporary finance. It examines how the traditional framework of Maqashid al-Shariah, encompassing the preservation of faith, life, intellect, progeny, and wealth, is interpreted and applied to guide the development and operation of Islamic financial products and institutions. The research critiques existing approaches, highlighting challenges such as the potential for formalistic interpretations that may deviate from the spirit of Maqashid, the complexities of adapting immutable principles to rapidly evolving financial innovations, and the tension between ethical ideals and market realities. It also explores opportunities for Maqashid-oriented finance to offer more equitable, sustainable, and socially responsible alternatives to conventional models, emphasizing areas like inclusive finance, ethical investments, and risk-sharing mechanisms. Ultimately, this abstract underscores the ongoing need for dynamic ijtihad and rigorous re-evaluation to ensure that modern Islamic finance genuinely embodies and effectively serves the holistic objectives of Shariah.